The first year of the sustainable finance disclosure regulation: an initial impact analysis on the European mutual fund market - Birkelbach, Anna Katharina (2022)
This study examines how the classification system of the Sustainable Finance Disclosure Regulation (SFDR) affects European mutual funds after its first year of application. First, the results show that larger funds with high sustainability ratings and in flows are more likely to classify as sustainable funds under the SFDR. Second, I find that the SFDR classification has no effect on fund returns, but a positive effect fund flows and sustainability ratings. The effects are strongest in Nordic countries and for Article 9 classification.